The collapse of the Soviet military - Odom, William E. (Yale University Press, 1998)
One of the great surprises in modern military history was the collapse of the Soviet Armed Forces in 1991 - along with the party-state with which it was inextricably intertwined. In this book, a distinguished United States Army officer and scholar traces the rise and fall of the Soviet military, arguing that it had a far greater impact on Soviet politics and economic development than was perceived in the West.